Double slope solar distiller with nanoparticles coated wick materials (International Journal of Food and Nutritional Sciences, 2021)
Experimental research is done on a revolutionary double slope wick type solar distiller (DSWSD) covered with lanthanum cobalt oxide (LaCoO3) nanoparticles doped in black paint. The jute wick surface is evenly speared with nano LaCoO3/black paint to increase solar irradiance absorption and facilitate successful desalination. At low saline water flow rates for the DSWSD, it is seen that there is an increase in internal HTCs as well as distilled yield. At a saline water flow rate of 0.05 kg/min, the suggested 5.40 and 3.85 kg/m2 per day, respectively.